Optimization of Coconut Plantations as a Source of Economic Empowerment for Santri in Islamic Boarding Schools - Kaharuddin; Fatimah, Siti; Sarwono; sarmiati; Kartika Devi, Erwina; Wargo; Al-Munip (CV. Civiliza Publishing, 2025)
This study examines the management of coconut plantations at Pondok Pesantren Wali Peetu in Desa Air Hitam Laut as an effort to strengthen the economic independence of the pesantren while serving as a holistic educational medium for santri (students). A qualitative research method employing a case study approach was used to explore the management processes, economic roles, and social impacts generated by the plantation. The findings indicate that the involvement of santri in all stages of coconut plantation activities not only produces significant income for the pesantren but also shapes the character, life skills, and leadership qualities of the santri in accordance with Islamic economic principles. This management model applies the “learning by doing” approach and context-based character education, integrating spiritual, technical, and social aspects. The coconut plantation management at the pesantren represents an important innovation that fills the gap in the traditional pesantren educational paradigm with a sustainable community-based economic empowerment approach. These findings are expected to serve as a reference for other pesantren seeking to optimize local resources for sustainability and santri empowerment